The Effectiveness Of The Special Job Fair’s Role At Smk Smti Banda Aceh In Enhancing Graduates Employability To The Business World - Zulkifli; Teuku Zulyadi; Nurfahmi (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
This study aims to see the effectiveness of the role of the Special Job Fair at SMK SMTI Banda Aceh in enhancing graduates’ employability to the Business World. This study uses a qualitative method by conducting interviews with the Industrial Relations Team and Alumni of SMK SMTI Banda Aceh and the Special Job Exchange Unit of SMK SMTI Banda Aceh from 2016 to 2021 covering the total number of graduates and the number of graduates working in The Business World, the graduates who are entrepreneurs, and the graduates who continue their education. The results showed that the role of the Special Job Fair SMK SMTI Banda Aceh in enhancingting graduates to The Business and Industrial was effective. This can be seen from the number of graduates who work and are being an entrepreneur,is increasing every year except for 2021. In 2021, there is a decrease in the number of graduates who work due to the COVID-19 pandemic situation. Many Special Job Fair program activities cannot be implemented due to efforts to overcome the covid-19 pandemic which has an impact on the distribution of graduates to The Business World.